Control of cart-ball system using state feedback and fuzzy logic controller - Basir, Budiman Azzali (2007)
A cart-ball system and the associated control design is an excellent platform for testing and evaluating different control techniques since such a system is an open-loop unstable system and demonstrates some basic concepts in control being nonlinear, multivariable and non-minimum phase. Industrial applications of such type of systems can be found in, for example, precise position control in production line. To control such a system, a controller should be designed to adjust the cart in a desirable manner through a DC motors. The cart position and ball angle form vertical are measured variables and manipulated variable is the horizontal force acting on the cart. The cart-ball mathematical model is derived and then linearized to be a linear model. The whole system then has been model in state space equation. The controller design is based on the theory of state feedback control approach and fuzzy logic control approach. Experimental results presented are useful for demonstrating practical aspects of the analysis. Furthermore, the cart-ball control system developed, is ideal for demonstrating the design and hardware implementation of optimal controllers based on modern control theory.